"Icelandic Music or Music from Iceland?" The Image of Icelandic Popular Music in British Media. (10th December 2021) - Sigurdardottir, Margret Sigrun; Gunnarsson, Kristjan Mar; Thoroddsen, Arnar Eggert
Abstract : This article aims to understand the image of Icelandic music as it is portrayed in three British media outlets and how this relates to the country of origin and the national image of Iceland. Using qualitative methods, the authors analysed 195 articles about Icelandic music. The image of Icelandic music has strong connections with Icelandic nature, whether imagined (other-worldly) or real (e.g., lava formations and glaciers). This is particularly true for Björk's and Sigur Rós's music. Findings indicate that these artists, specifically the eccentric Björk, have paved the way for a symbolically loaded "Icelandic sound" and, accordingly, have built a strong image of Icelandic music. At the same time, emerging popular artists from Iceland, such as Of Monsters and Men and Kaleo, go against this trend by following a different path which does not match established expectations for Icelandic music, thus shifting the focus from Icelandic music towards music from Iceland.